TAKING POLICY SERIOUSLY: WHAT SHOULD INDONESIAN GOVERNMENT DO TO STRENGTHEN ACEH TRUTH AND RECONCILIATION COMMISSION? - Herlambang P Wiratraman; Sri Lestari Wahyuningroem; Manunggal K. Wardaya; Dian P. Simatupang (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2020)
This article discusses three key questions. First, what and how is the development of policies and legal protection that can be the support for the central government in implementing the Aceh Truth and Reconciliation Law? Second, how is the Aceh TRC and Human Rights Court as a mechanism of justice can mutually strengthen the protection of human rights for victims and their families? Third, how is to build solid legal relationships among state institutions to fortify the TRC’s recommendation regarding reparation? This article is written based on research and focus group discussion and is aimed to encourage several legal policy developments oriented as solutions to the limited efforts to protect and fulfill victims, particularly related to reparation and restoration of their rights. It also emphasizes the legal position of the basic national political and legal context, associated as a reminder to the dignity of the Memorandum of Understanding of Helsinki for the future of Aceh. Abstrak: Artikel ini mendiskusikan tiga pertanyaan kunci, yakni pertama, apa dan bagaimana pengembangan kebijakan dan payung hukum yang dapat menjadi dukungan Pemerintah Pusat terhadap pemberlakuan KKR Aceh? Kedua, bagaimana secara institusional kelembagaan KKR Aceh dan Pengadilan HAM sebagai mekanisme keadilan dapat saling memperkuat perlindungan HAM bagi korban dan keluarganya? Ketiga, bagaimana membangun relasi hukum yang kuat antar Lembaga negara untuk memperkuat rekomendasi KKR terkait reparasi? Dihasilkan dari proses riset dan diskusi grup terarah, artikel ini mendorong sejumlah pengembangan kebijakan hukum yang diorientasikan sebagai jalan keluar atas terbatasnya upaya perlindungan dan pemenuhan bagi korban, terutama terkait reparasi dan pemulihan hak-haknya. Serta, menegaskan posisi hukum atas konteks politik hukum nasional yang mendasar dikaitkan kembali sebagai pengingat marwah MOU Helsinki bagi masa depan Aceh. Kata Kunci: Komisi Kebenaran dan Rekonsiliasi, Hukum Hak Asasi Manusia, Kebijakan Pemerintah Indonesia, Pemerintah Aceh